(6 x 5) / 2 = 3 x 5 so (30/2)=(3 x 5) 15=15
3 x 2- 5 = 1 3x 2 =6 6 - 5 = 1 so one is the answer
It is about 2.236You want a number X such that X^6=125.125= 5*5*5= 5^3.So, X^6=5^3.3=6*(1/2)= 6/2.So, X^6= 5^(6/2).Take the sixth root on both sides of the equation. This gives:X= 5^(1/2)= Sqr Rt (5) is the number.
15 x 2 3 x 10 10 x 3 2 x 15 6 x 5 5 x 6
5/6 x 12/5 = 2
thirty 30 = 2 x 15 = 3 x 10 = 5 x 6 = 6 x 5 furthermore, of 2 3 5 6 the 2 and 3 are not needed, as 6 is already 2 x 3 so only 5 and 6 are in question.
1/2 x + 6 = 11 1/2 x + 6 - 6 = 11 - 6 1/2 x = 5 2*(1/2 x) = 5*2 x = 10 1/2 of 10 is 5, 5 plus 6 is 11 QED
2x - 6 = 4 2x = 4 + 6 = 10 x = 10/2 = 5 ∴ x = 5
2x2 - 5x + 6 = ?x = -1(2 x (-1)2) - (5 x -1) + 6 = ?(2 x 1) - (-5) + 6 = ?2 + 5 + 6 = 13
- 5 - x + 2 - x + 6 - x + 10 - x = -5 + 2 + 6 + 10 - x - x - x - x = 13 - 4x
That is calculated as (6 x 5 x 4) / (1 x 2 / 3).That is calculated as (6 x 5 x 4) / (1 x 2 / 3).That is calculated as (6 x 5 x 4) / (1 x 2 / 3).That is calculated as (6 x 5 x 4) / (1 x 2 / 3).
12-5(6-3x)2(6-x)-8x = -30x^2 + 232x -348
To find the sum of two and one third plus five sixths of one and two fifths, first convert all the mixed numbers to improper fractions. Two and one third is equivalent to 7/3, one and two fifths is equivalent to 7/5. Next, find five sixths of 7/5 which is 35/30 or 7/6. Finally, add 7/3 and 7/6 to get 21/6 + 7/6 = 28/6 which simplifies to 4 and 2/6 or 4 and 1/3. Therefore, the sum is 4 and 1/3.
x = 5 x-2y = 6 => x = 6+2y 6+2y = 5 2y = 5-6 2y = -1 y = -1/2 and x = 5 Point of intersection: (5, -1/2)
12-5(6-3x)2(6-x)-8x = -30x^2 + 232x -348
656,562 =(6 x 100000) + (5 x 10000) + (6 x 1000) + (5 x 100) + (6 x 10) + (2 x 1) or(6 x 105) + (5 x 104) + (6 x 103) + (5 x 102) + (6 x 101) + (2 x 100)
656,562 =(6 x 105) + (5 x 104) + (6 x 103) + (5 x 102) + (6 x 101) + (2 x 100) OR(6 x 100,000) + (5 x 10,000) + (6 x 1,000) + (5 x 100) + (6 x 10) + (2 x 1)